2006
DOI: 10.1016/j.molcel.2006.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Maintenance of High p53 Acetylation by PTEN

Abstract: Earlier studies have shown that PTEN regulated p53 protein stability both in a phosphatase-dependent manner through antagonizing Akt-Mdm2 pathway and in a phosphatase-independent manner through interacting with p53. In this study, we report that PTEN forms a complex with p300 in the nucleus and plays a role in maintenance of high p53 acetylation in response to DNA damage. Furthermore, p300 is required for nuclear PTEN-regulated cell cycle arrest. Interestingly, however, p53 acetylation was found to promote PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 43 publications
(60 reference statements)
6
130
0
3
Order By: Relevance
“…Moreover, nuclear PTEN, but not cytoplasmic PTEN, induced p300-dependent G1 arrest in U2OS cells. 57 Collectively, these observations show that PTEN's subcellular localization is cell cycle-dependent and suggests that alterations in the regulation of PTEN import and export to and from the nucleus contribute to its tumor suppressor function.…”
Section: Pten-oncoprotein Networkmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, nuclear PTEN, but not cytoplasmic PTEN, induced p300-dependent G1 arrest in U2OS cells. 57 Collectively, these observations show that PTEN's subcellular localization is cell cycle-dependent and suggests that alterations in the regulation of PTEN import and export to and from the nucleus contribute to its tumor suppressor function.…”
Section: Pten-oncoprotein Networkmentioning
confidence: 89%
“…45 Other studies have implicated phosphatase-independent functions of PTEN within the nucleus including protein-protein interactions that modulate the activity and stability of p53. 43,46 It has been suggested that nuclear PTEN's growth-suppressing activities may be mediated through p53 47 , which is dependent on p300 interaction 46 , the inhibition of MSP58 49 or maintaining chromosomal integrity. 48 It has been shown that nuclear PTEN's growth-regulatory function depends on its lipid phosphatase activity.…”
Section: Role Of Nuclear Pten In Glioblastomamentioning
confidence: 99%
“…Given the ability of PTEN to indirectly stabilize p53 protein through antagonizing the Akt-MDM2 pathway (4,10,26) or by directly increasing p53 acetylation (27), decreased p53 activity in PTEN-deficient tumor cells should be expected and would explain the comparably preferential activity of caffeine in radiosensitizing p53-deficient (Table 1A; refs. 23,24) and PTEN-deficient tumor cells (Table 1A; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The second messenger PIP3 binds to a subset of pleckstrin homology domain-containing proteins, enabling the plasma membrane recruitment and activation of target proteins (Frech et al, 1997;Klarlund et al, 1997). Intriguingly, PIP3 is also found in the nucleus, along with PTEN and other pathway components, revealing a more complex view of the PTEN network (Tanaka et al, 1999;Liu et al, 2005a, b;Deleris et al, 2006;Gil et al, 2006;Li et al, 2006;Lindsay et al, 2006;Trotman et al, 2006Trotman et al, , 2007Baker, 2007;Shen et al, 2007;Chang et al, 2008). PI3K signaling induces a diverse array of cancerpromoting events including the regulation of the protein kinases PDK1 and AKT, which directly bind to and are activated by PIP3 (Alessi et al, 1997;Currie et al, 1999).…”
Section: Pten/pi3k Signaling Perturbations In Cancermentioning
confidence: 99%
“…Not only do PTEN and p53 participate in many of the same cellular processes, they also physically interact and regulate each other. The physical association between p53 and PTEN affects the p53 acetylation state and its ability to bind DNA (Freeman et al, 2003;Li et al, 2006;Chang et al, 2008). The p53 transcription factor also binds to the PTEN promoter and transactivates PTEN gene expression (Stambolic et al, 2001).…”
Section: Pten/pi3k Signaling Perturbations In Cancermentioning
confidence: 99%